Testing the Rationality of Survey Data Using the Weighted Double-Bootstrapped Method of Moments - Jeong, Jinook; Maddala, G. S. (The Review of Economics and Statistics, 1996)
Jinook Jeong, G. S. Maddala, Testing the Rationality of Survey Data Using the Weighted Double-Bootstrapped Method of Moments, The Review of Economics and Statistics, Vol. 78, No. 2 (May, 1996), pp. 296-302